Le fratture dell’omero prossimale in età pediatrica - Bertoni, G.; Lelio, E. (Lo Scalpello - Journal, 2018)
FRACTURES OF THE PROXIMAL HUMERUS IN THE PEDIATRIC AGEIn the paediatric population, sports, falls and car accidents can result in proximal humerus fractures. Since theproximal humeral growth plate is responsible for up to 80% of the growth of the humerus, remodelling of thesefractures in children is enormous: the younger the patient, the higher the potential for remodelling. Most proximalpaediatric humeral fractures can be treated successfully by closed means. However, some patient factors or fracturecharacteristics may prompt for surgical treatment.